Implementasi Kurikulum Merdeka Belajar Kampus Merdeka (MBKM) melalui Analisa Problematika - Cindy Inkka Rahmadia; Annisa Agustia Rahma; Muhammad Yusqi Shoubil Haq (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Universities as an important role in the formation and improvement of the quality of human resources as a pillar of development in the country. This needs to be considered in the face of globalization, in its implementation, the government seeks the welfare of students in the Merdeka Campus program which is supervised by the Ministry of Education and Culture which aims to provide real experience for students in preparation for the world of work. Related to this, this research aims to determine the implementation of the Merdeka Learning program at the independent campus in universities and the problems faced at Bhayangkara University. This study uses the type of approach used in this study is a qualitative approach, using the observation method. the research subject is a data source that provides information related to research problems, then the research subject you choose and enter the criteria we are looking for is the head of the department / study program at Bhayangkara University. Techniques of collecting data and determining the subject of this research we use interview techniques and literature studies. The results of this study indicate that the University of Bhayangkara has undergone curriculum adjustments and implementations carried out by the campus, so that there are many problems and obstacles faced by the study of the Law program at one of these private universities in implementing the Merdeka learning curriculum on an independent campus related to programs the program in it.